A potential role for overdominance in the maintenance of colour variation in the Neotropical tortoise beetle, Chelymorpha alternans. (25th March 2021) - Strickland, Lynette R.; Fuller, Rebecca C.; Windsor, Donald; Cáceres, Carla E.
Abstract: The presence of persistent polymorphisms within natural populations elicits the question of how such polymorphisms are maintained. All else equal, genetic drift and natural selection should remove genetic variants from populations. Disassortative mating and overdominance are potential mechanisms for maintaining variation within populations. Here, we consider the potential role of these mechanisms in maintaining variation in colour pattern in the tortoise beetle, Chelymorpha alternans . Five colour morphs distinguished by elytral and pronotal coloration are largely determined by a single locus of large effect with four segregating alleles. As many as four morphs co‐occur in natural populations. We first assessed whether disassortative mating might maintain this polymorphism. To test for assortative and disassortative mating, we paired females with two males, one with the same colour pattern as the female and one with a different colour pattern and examined the colour patterns of the offspring. We found strong evidence for random mating as a function of colour pattern. We next assessed whether differences in offspring survival among assortative and disassortative male‐female pairs maintain colour variation. Crosses involving disassortative pairings had significantly higher offspring survival during development and resulted in more adult progeny. This result is consistent with the effects of overdominance, whereby outcrossed individuals have higher fitness than their homozygous counterparts. Overall, differences in offspring survival appear to play a greater role in maintaining polymorphisms than nonrandom mating in species. Abstract : Overdominance contributes to the maintenance of multiple color patterns within populations in the Neotropical tortoise beetle, Chelymorpha alternans. Larvae from disassortative mating pairs are twice as likely to survive to adulthood than larvae from assortative pairings. The genetics of the color pattern are known, allowing us to infer which individuals are homozygotes or heterozygotes. Surprisingly, mating is random with respect to color pattern, and females have increased clutch size when mating with males of their own phenotype. In this system, there are either constraints that prevent the evolution of adaptive mate choice or additional fitness consequences of mate choice besides those shown here.